READING STRATEGIES FOR ADULT READERS OF ENGLISH AS A FOREIGN LANGUAGE COMPARING SUCCESSFUL AND LESS SUCCESSFUL READERS - Aripbayeva Gulchehra (Journal of new century innovations, 2023)
Abstract: This article explains the reading techniques for proficient and less proficient readers. The main goal was to investigate how their adult characteristics might affect how they used their academic reading strategies. In addition some useful strategies for adult readers was discussed.